2018
DOI: 10.1007/s12603-018-1098-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mastery and Caregiving Competence in Protecting against Burden, Anxiety and Depression among Caregivers of Frail Older Adults

Abstract: ObjectiveStudies suggest the protective effect of mastery and caregiving competence against psychological stressors of caregiving in the context of dementia, although the interplay between the two with caregiver outcomes is not well understood. This study examines the independent and moderating impact of mastery and caregiving competence on burden, anxiety and depression among caregivers of older adults with frailty-related care needs.Design, Setting and ParticipantsThis is a cross-sectional study of 274 older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 45 publications
6
42
0
2
Order By: Relevance
“…Our finding that improvements in QOL and reductions in depression symptoms may have occurred indirectly through improvements in self‐efficacy for caregivers randomly assigned to BMT‐CARE extends our understanding of the potential relationships between caregiver self‐efficacy and psychosocial outcomes 26 . A sense of mastery and caregiving competence have been associated with reduced caregiving burden and anxiety and depression symptoms in other caregiving populations; however, few studies have explored intervention mechanisms in the HCT caregiver setting 27 . In 1 study, a problem‐solving education intervention among caregivers of patients who received allogeneic HCT led to improvements in self‐efficacy, distress, and fatigue 18 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our finding that improvements in QOL and reductions in depression symptoms may have occurred indirectly through improvements in self‐efficacy for caregivers randomly assigned to BMT‐CARE extends our understanding of the potential relationships between caregiver self‐efficacy and psychosocial outcomes 26 . A sense of mastery and caregiving competence have been associated with reduced caregiving burden and anxiety and depression symptoms in other caregiving populations; however, few studies have explored intervention mechanisms in the HCT caregiver setting 27 . In 1 study, a problem‐solving education intervention among caregivers of patients who received allogeneic HCT led to improvements in self‐efficacy, distress, and fatigue 18 .…”
Section: Discussionsupporting
confidence: 51%
“…26 A sense of mastery and caregiving competence have been associated with reduced caregiving burden and anxiety and depression symptoms in other caregiving populations; however, few studies have explored intervention mechanisms in the HCT caregiver setting. 27 In 1 study, a problem-solving education intervention among caregivers of patients who received allogeneic HCT led to improvements in self-efficacy, distress, and fatigue. 18 A meta-analysis and systematic review of family caregiver interventions in oncology showed improvement in self-efficacy with small to medium effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…However, before culturally-responsive programs for carers can be developed and evaluated, the unique needs of this population must be understood. Important attributes in managing the carer role include resilience and empowerment, and the mastery of skills such as problem solving and adaptation as necessary (Chan, Glass, Chua, Ali, & Lim, 2018;Petriwskyj, Parker, O'Dwyer, Moyle, & Nucifora, 2016;Sakanashi & Fujita, 2017;Teahan et al, 2018). Conversely, depression, anxiety, and perceived burden (Petriwskyj et al, 2016), are frequently measured outcomes in carer research and inversely related to positive notions of health, resilience and empowerment.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pearlin, mastery can reduce the impact of stress either via people with high mastery perceiving stressors in a less menacing way, or with it acting as a self-fulfilling prophecy (25). Recent research found that lower levels of mastery was associated with higher levels of burden, which eventually lead to higher levels of depression (26, 27). Mastery was also shown to attenuate the effects of stress on health across time, while low mastery was associated with depressive symptoms and poor health (28).…”
Section: Introductionmentioning
confidence: 99%